The road to excellence: Expert performances in tennis and alpine skiing - Marconi, M.; Conzelmann, A. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Within different domains (e.g. music) Ericsson (1996) described the "road to excellence". Taking this expertise research into consideration, the career path of top-performance ath-letes in tennis and alpine skiing were analysed in two different studies with a retro-spective approach. The career in sports is viewed as part of the entire life-course (Mayer, 1990) that embraces various careers in (individual) fields of life. The sports career is em-bedded in the top-performance sports system but also involves a certain dependency on other aspects of life (e.g. family, profession). Methods: The data was collected by postal enquiry. The questionnaires, adapted to the different characteristics of tennis and alpine skiing, were sent to active and former athletes (tennis: n=70; alpine skiing: n=51). These include questions concerning activities and incidents in various areas of life, particularly sports, but also family and education / profession. Results: Certain steps from one to the other period in a career in sports can vary considerably, for example `age at the beginning with sports` (tennis/alpine skiing: mean=6.9/3.4, range=3-12/2-7) or `age at the beginning with adult competition` (tennis and alpine skiing: mean=15.4, range=13-18). The individual career paths show partly distinct differences compared to the career path intended in the talent development programmes, diverse chronological sequences in performance development and gender-specific charac-teristics. Compared to less successful athletes, top athletes have a higher rate of development and, from the beginning of their career, increased training units close to competition. Discussion: The talent development programmes should consider the individuality of the career paths as well as the gender-specific aspects. Furthermore, it is recommended that the rate of development is determined by testing the athletes over time. Finally, the specialisation in the specific kind of sport should start as early as possible.